PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE BERBANTU MEDIA GAMBAR TERHADAP HASIL BELAJAR IPAS KELAS V SEKOLAH DASAR - Kamala, Septia; Lingga, Leny Julia (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study was motivated by the limited and less varied use of learning models and media, which has not fully supported the teaching and learning process. The aim of this study was to determine the effect of the Scramble-type cooperative learning model assisted by image media on students’ learning outcomes in Integrated Science and Social Studies (IPAS) in fifth grade at SD Negeri 022 Jaya Mukti. This research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The population consisted of 113 students, and the sample of 28 students was selected using purposive sampling. Data were collected using test instruments. Hypothesis testing was conducted using a paired samples t-test to examine the effect of the independent variable on the dependent variable. The results showed that the implementation of the Scramble-type cooperative learning model assisted by image media had a positive effect on improving students’ learning outcomes. This was supported by the paired samples t-test result with a significance value of 0.000 < 0.05, indicating that the alternative hypothesis was accepted. In addition, the effect size calculated using Cohen’s d was 2.72, indicating a very large effect. In conclusion, the applied learning model is highly effective in enhancing students’ IPAS learning outcomes.